PENERAPAN LKS BERBASIS CTL PADA PERUBAHAN MATERI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PAKET B DI MASA COVID – 19 PADA SPNF KOTA BANDA ACEH - Prasetia, Aulia; Ismulyati, Sri; Damayanti, Rizki (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2022)
A research has been carried out with the theme "Implementation of CTL-Based Worksheets on Material Changes to Increase Student Learning Motivation in Package B during the Covid-19 Period at SPNF Banda Aceh City". This study aims to determine the effectiveness of the application of Contextual Teaching and Learning (CTL)-based LKS on material changes used in SPNF SKB Banda Aceh and to determine student responses to the application of Contextual Teaching And Learning (CTL)-based LKS on material changes in SPNF SKB. Banda Aceh City. The benefits of this research are for students, the LKS Module can be used as a learning resource, so that it can increase interest in learning chemistry, and can relate the material to the surrounding environment; For teachers, the LKS Module can be used as teaching materials to assist teachers in creating interesting and interactive learning situations; For schools, this research is expected to contribute to improving the conditions of chemistry learning so that it can create a better quality of education in the future. In this research, the method of observation, test (pre-test and post-test) and questionnaire. The results of this study indicate a positive response as evidenced by the data generated.